Caracterización química-biológica de granos y propagación in vitro de Coffea arabica - Gallardo Ignacio, Javier (Universidad Autónoma Metropolitana, 2024)
The use and consumption of coffee began in Ethiopia as food for slaves and travelers. In the Arabian Peninsula, it started to be consumed in the form of liqueur and infusions based on roasted beans, eventually becoming a popular drink due to its stimulating effects. Its distribution in Europe further favored the consumption and commercialization of coffee. The coffee plant belongs to the Rubiaceae family and the Coffea genus, with 103 known species. Commercial production is primarily based on C. arabica and C. canephora, both of which are grown in countries located between the Tropic of Cancer and the Tropic of Capricorn. Brazil, Vietnam, and Colombia are the main producers, while Mexico ranks as the 10th largest producer. Mexico is known for its quality and organic coffee, with favorable altitude, soil, and climate conditions in the states of Chiapas, Veracruz, Puebla, Oaxaca, and Guerrero. Coffee in Mexico is mainly processed by wet means, with some areas employing dry processing methods, such as in the state of Guerrero where artisanal producers market coffee within their region and nationally. Mexican standards that regulate the commercialization of roasted and ground coffee are NMX-F-013-SCFI-2010 and PROY-NOM-255-SE-2021. The physical and chemical composition of the roasted beans gives the infusions several characteristics of aroma and flavor, as well as other attributes for stimulating, antioxidant, anti-inflammatory effects among others. In this thesis project, the nutritional-chemical composition and biological evaluation of two commercial coffees from the Cooperativa Cafeticultores ME PHAA de la Montaña was determined. As well, it was carried out an in vitro propagation process of Coffea arabica variety Oro Azteca. The nutritional composition of medium roast coffee (CTM) and dark roast coffee (CTO) complies with the indications for moisture and ash according to NMX-F-013- SCFI-2010, while the fat content does not meet the standard. Chlorogenic acid (CGA) was identified and quantified in the green beans of the 3 varieties: Typica, Bourbon, and Oro Azteca, with the latter 2 showing the highest content. After the roasting process, the CGA content was reduced in the CTO. Caffeine content showed a similar trend between green beans varieties, with an increase observed after roasting. Based on the PROY-NOM-255-SE-2021 standard and sensory tests, CTM beans were classified as natural specialty coffee, while CTO was considered premium natural coffee. CTM and CTO extracts showed antioxidant effects in DPPH, ABTS, and FRAP tests. Cytotoxicity tests on the 3T3-L1 fibroblast cell line showed no toxic effect, indicating the absence or low content of toxic compounds in the roasted beans. Nodal segments of C. arabica variety Oro Azteca formed shoots after 3 months of cultivation supplied with benzylaminopurine (BAP) treatments or in combination with indoleacetic acid (IAA) as growth regulators. Individualized shoots were rooted using IAA, with seedlings achieving an 85% survival rate after transplantation to the greenhouse. The results show the current quality of the commercial products of this cooperative and the areas of opportunities for improvement to meet the established requirements, with the obtaining of seedlings of the Oro Azteca variety through in vitro culture, a process of constant renewal of the crops can be initiated.; El uso y consumo del café comenzó en Etiopía como alimento para esclavos y viajeros. En la Península Arábiga comenzó a consumirse en forma de licor e infusiones a base de granos tostados, llegando a ser una bebida popular debido a sus efectos estimulantes. Su distribución en Europa favoreció aún más el consumo y comercialización del café. La planta del café pertenece a la familia Rubiaceae y al género Coffea, con 103 especies conocidas. La producción comercial se basa principalmente en C. arabica y C. canephora, las cuales se cultivan en países ubicados entre el Trópico de Cáncer y el Trópico de Capricornio. Brasil, Vietnam y Colombia son los principales productores, mientras que México se ubica como el décimo productor. México es conocido por su calidad y café orgánico, con condiciones favorables de altitud, suelo y clima en los estados de Chiapas, Veracruz, Puebla, Oaxaca y Guerrero. El café en México se procesa principalmente por vía húmeda en algunas áreas emplean métodos de procesamiento en seco como en el estado de Guerrero, donde los productores artesanales comercializan café dentro de su región y a nivel nacional. Las normas mexicanas que regulan la comercialización de café tostado y molido son NMX-F-013-SCFI-2010 y PROY-NOM-255-SE-2021. La composición física y química de los granos tostados confiere a las infusiones varias características de aroma y sabor, así como otros atributos por sus efectos estimulantes, antioxidantes, antiinflamatorios entre otros. En este proyecto de tesis se determinó la composición nutricional-química y la evaluación biológica de dos cafés comerciales de la Cooperativa Cafeticultores ME PHAA de la Montaña, asimismo, se llevó a cabo un proceso de propagación in vitro de Coffea arabica variedad Oro Azteca. La composición nutricional del café de tueste medio (CTM) y café de tueste oscuro (CTO) cumple con las indicaciones de humedad y cenizas según NMX-F-013-SCFI- 2010, mientras que el contenido de grasa no cumple con la norma. Se identificó y cuantificó el ácido clorogénico (ACG) en los granos verdes de las 3 variedades: Típica, Borbón y Oro Azteca, siendo estas 2 últimas las que mostraron el mayor contenido. Después del proceso de tostado, el contenido de ACG se redujo en el CTO. El contenido de cafeína mostró una tendencia similar entre las variedades de granos verdes, observándose un aumento después del tostado. Con base en la norma PROY-NOM-255-SE-2021 y las pruebas sensoriales, los granos de CTM se clasificaron como café de especialidad natural, mientras que el CTO se consideró café natural premium. Los extractos de CTM y CTO mostraron efectos antioxidantes en las pruebas DPPH, ABTS y FRAP. Las pruebas de citotoxicidad en la línea celular de fibroblastos 3T3-L1 no mostraron ningún efecto tóxico, lo que indica la ausencia o bajo contenido de compuestos tóxicos en los granos tostados. Los segmentos nodales de C. arabica variedad Oro Azteca formaron brotes después de 3 meses de cultivo utilizando tratamientos con bencilaminopurina (BAP) o en combinación con ácido indolacético (AIA) como reguladores del crecimiento. Brotes individualizados se enraizaron con AIA y las plántulas lograron una tasa de supervivencia del 85% después del trasplante al invernadero. Los resultados muestran la calidad actual de los productos comerciales de esta coperativa y las areás de oportunidades de mejora para poder cumplir con los requirimientos establecidos, con la obtención de plantulas de la variedad Oro Azteca mediante el cultivo in vitro se puede inciar un proceso de renovación constante de los cultivos.